Evaluasi Hadging/Kontrak Forwardterhadap Gejolak Kurs : Study Mandiri - Suwandri, Suwandri (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2003)
The difference between domestic and foreign interest rate which preceded exchange rate fluctuation has a consequence, namely standard deviation of forward exchange is smaller than standard deviation of spot exchange. That is why, forward contract will decrease the deviation of cash flow as the result of change rate fluctuation